Photoactive meso-tetra(4-pyridyl)porphyrin-tetrakis-[chloro(2, 2′bipyridine)platinum(ii) derivatives recognize and cleave DNA upon irradiation. Issue 5 (18th January 2017) - Oliveira, Vanessa A.; Iglesias, Bernardo A.; Auras, Bruna L.; Neves, Ademir; Terenzi, Hernán
Abstract : Photoactive platinum porphyrins may be interesting as photosensitizers in photodynamic therapy and photochemotherapy, and we demonstrate their activity towards DNA cleavage under exposure to light. Abstract : In this work, we evaluate the interaction of the peripheral Pt(bpy)Cl + substituted porphyrins, H2 PtPor andZnPtPor with DNA using UV-vis, emission fluorescence, CD spectroscopy, and DNA melting properties altered by the Pt(ii )–porphyrinoid compounds. Additionally, we observe the ability of these porphyrin derivatives to generate 1 O2 and to efficiently photocleave plasmid DNA upon visible light irradiation based on a mixed (oxidative/hydrolytic) mechanism.